Empowering Creation in Freedom: The Kenosis of the Holy Spirit - Putrawan, Bobby Kurnia; Uroko, Favour C. (LPPM - Sekolah Tinggi Teologi Indonesia Jakarta, 2025)
Contemporary conceptions of divine power are frequently framed in terms of sovereignty and unilateral control. This article proposes an alternative theological model by examining the kenosis of the Holy Spirit within the context of creation. The central objective is to explore how the Spirit’s self-emptying presence constitutes a mode of divine empowerment that operates not through coercion but by enabling the freedom of creation. Employing a reflective theological methodology, this study integrates biblical exegesis—particularly of Genesis 1:2 and Psalm 104:30—with systematic theological reflection and critical engagement with the works of key theologians such as Jürgen Moltmann, Hans Urs von Balthasar, John Zizioulas, and Karl Barth. The analysis demonstrates that the kenotic action of the Holy Spirit should not be construed as divine absence but rather as a purposeful self-limitation that nurtures a relational and participatory cosmos. Accordingly, this study contributes to pneumatological discourse by articulating a paradigm of divine power grounded in relationality, humility, and ethical responsibility, offering constructive implications for theology, anthropology, and ecology.